ENGLISH: The Educational and Intellectual Situation of Muslims in ASEAN - Layma Mehmood; Dr. Sana Jadoon (Al-Dalili, 2025)
The educational and intellectual landscape of Muslims in the ASEAN (Association of Southeast Asian Nations) region reflects a complex interplay of diversity, resilience, and transformation. With over 250 million Muslims across countries such as Indonesia, Malaysia, Brunei, Thailand, and the Philippines, the region showcases a rich mosaic of religious and secular educational systems that contribute significantly to Southeast Asia’s cultural and academic fabric. Significant progress has been made in nations like Malaysia and Indonesia in harmonizing Islamic values with contemporary education. Nevertheless, challenges persist in areas such as equitable access, academic quality, and intellectual autonomy. In minority contexts—particularly Thailand and the Philippines Muslims often encounter structural marginalization, which constrains both educational advancement and the freedom of intellectual expression. Historical legacies, political dynamics, and socio-economic disparities further shape the educational trajectories of Muslim communities. Emerging developments include the establishment of Islamic universities, regional and international academic collaborations, the growing use of digital learning technologies, and a renewed interest in classical Islamic sciences alongside modern disciplines. The expanding role of Muslim women in education and the impact of transnational Islamic movements on local reform initiatives also form critical aspects of this evolving landscape. Findings from this research highlight both notable achievements and persisting deficiencies in Muslim education across ASEAN. These insights aim to inform regional policy debates and offer strategic recommendations for fostering inclusive, high-quality, and context-sensitive educational frameworks that empower Muslim communities throughout Southeast Asia.